Imaging ionic flux through individual pores in droplet interface bilayers - Szabo, M (2016)
Optical measurements of ion flux are a powerful technique when studying the functional properties of ion channels and the dynamics of pore formation in biological membranes. The simultaneous read-out of optical single channel recordings (oSCR) provides an alternative way of measuring electrical activity and is more feasible than parallelising electrical measurements. Channel activity is monitored with ion specific indicator dyes whose response is proportional to the magnitude of the current. Here, two novel applications of oSCR in a droplet interface bilayer model membrane system are presented. Firstly, a technique for potassium-flux imaging through individual electropores is developed. Three indicator dyes are characterised with fluorescence spectroscopy and oSCR of potassium-flux are shown for the first time. Dynamic fluorescence response when applying a voltage protocol can be observed while monitoring currents through several pores in parallel. The response time is between 2.5-10 s and the minimum resolvable current is estimated to be -2 nA. Secondly, pore formation in the presence of four antimicrobial peptides (melittin, magainin 2, alamethicin, indolicidin) is visualised by calcium-flux imaging combined with single-molecule imaging of labelled peptides in the same membrane region. Calculations of radial distribution functions show a uniform distribution of peptides on the membrane surface. Punctate poration events observed with calcium-flux most likely originate from barrel-stave (alamethicin) or toroidal pores (melittin and magainin 2), whereas indolicidin does not promote pore formation. The techniques developed in this thesis are an important contribution to the field of oSCR.